2005
DOI: 10.1111/j.1439-0264.2005.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Mesodermal and Mesenchymal Origin of Myotomal Muscles in Pike (Esox lucius: Teleostei)

Abstract: During the myotomal myogenesis in pike (Esox lucius) two phases of muscle differentiation can be distinguished. In the first phase, the somite cells-derived stock, the primary myoblasts (of mesodermal origin), fuse to form multinucleate myotubes. Participation of myotomal cells of mesodermal origin is insufficient for further muscle development. In the second stage mesenchymal cells migrate, via myosepts, into the myotome between myotubes. Immunocytochemical detection of proliferating cell nuclear antigen (mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
1
12
0
2
Order By: Relevance
“…thymallus (Merkel, 1995), B. rerio (Waterman, 1996, after Johnston, 2001, R. frisii meidingeri (Stoiber and Sänger, 1996), E. lucius (Kacperczyk and Daczewska, 2006), show the same structural pattern. They are built by a layer of tightly adjoining circumferential cells covering a centrally located group of more loosely arranged round cells.…”
Section: Early Events Of Myogenesismentioning
confidence: 75%
See 2 more Smart Citations
“…thymallus (Merkel, 1995), B. rerio (Waterman, 1996, after Johnston, 2001, R. frisii meidingeri (Stoiber and Sänger, 1996), E. lucius (Kacperczyk and Daczewska, 2006), show the same structural pattern. They are built by a layer of tightly adjoining circumferential cells covering a centrally located group of more loosely arranged round cells.…”
Section: Early Events Of Myogenesismentioning
confidence: 75%
“…In fishes, fusion-associated vesicles have been observed during myogenesis in O. mykiss (Nag and Nurse, 1972), M. glutinosa (Sandset and Konrneliussen, 1978) and Th. thymallus (Merkel, 1995), E. lucius (Kacperczyk and Daczewska, 2006). Fusion-associated vesicles have been also found under the plasma membrane in the satellite cells of the sonic muscle in toadfish (Opsanus tau) (Loesser'et al, 1997).…”
Section: Cells Involved In Myotomal Muscle Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…This is indicated by the presence of numerous vesicles in the subsarcolemmal sarcoplasm of muscle fibers and the partial fusion of muscle fiber and mononucleated cell plasma membranes. Similar vesicles have been found below the plasmalemma of fusing chick myoblasts in vitro (Kalderon and Gilula, 1979) and in vivo during teleost myotomal myogenesis in the European grayling, Thymallus thymallus, and pike, Esox lucius (Merkel, 1995;Kacperczyk and Daczewska, 2006). According to Orlov et al (1989), who analyzed chick myogenic cell fusion in TEM, the fusion-associated vesicles are always present below the plasmalemma of more advanced myogenic cells.…”
Section: Growth Of Muscle Fibersmentioning
confidence: 79%
“…Previous work revealed that the earliest populations of presumptive myogenic cells arose from several zones of the early somite (Vegeetti et al, 1990;Rowlerson and Veggetti, 2001). It has also been suggested that muscle growth becomes powered by mesenchymal cells, which migrate by means of myosepta into myotomes (Stoiber and Sä nger, 1996;Kacperczyk and Daczewska, 2005).…”
Section: Muscle Stem Cells and Muscle Growth In Lower Vertebratesmentioning
confidence: 99%